Risk Factors of Acute Renal Cortical Lesions in Scintigraphy in Children with Urinary Tract Infection - Nikbakhsh, Ali; Mahmoodzadeh, Hashem; Hejazi, Sasan; Noroozi, Mehran; Sadegy, Ebrahim; Gazavy, Ahad; Gheibi, Shahsanam; Abasi, Ezatalah; Aminfarzanh, Nazanin; Nasimfar, Amir (Journal of Pediatric Nephrology, 2015)
Introduction: Urinary Tract Infection (UTI) is one of the most common pediatric infections. UTI may create cystitis or pyelonephritis by involving bladder or renal parenchyma, respectively. Pyelonephritis, especially in pediatric patients, can lead to scar formation in kidneys and consequent complications such as hypertension, proteinuria, dysfunction and chronic renal insufficiency. The current study aimed to determine risk factors of acute rental cortical lesions in renal scintigraphy in children with UTI. Materials and Methods: Fifty-three patients with significant renal cortical lesions and 53 cases without significant renal cortical lesions were compared based on the intensity of findings of DMSA scintigraphy within the first two weeks of diagnosis. Patients were divided into three groups of 1 month to 2 years, 2 to 4 years and 4 to 10 years. Results: Of 106 patients, 11 males (20.8%) and 42 females (79.2%) had significant acute renal cortical lesions, whereas 15.1% of males and 84.9% of females had no significant acute renal cortical lesions. There was a significant difference in the degree of fever, the average interval between the onset of fever and treatment, mean level of CRP, leukocytosis and ESR in the two studied groups. The presence of Vesicoureteral Reflux (VUR), low initial hemoglobin and low initial BMI as random findings were associated with significant renal cortical lesions. Gender, age, grade of VUR and type of organism in urine culture had no significant association with significant renal cortical lesions. Conclusions: In this study, delaying in treatment, high degree fever, leukocytosis, high initial ESR and CRP, existence of VUR and low initial BMI and hemoglobin levels were associated with an increase in the value of acute renal cortical lesions, so in these cases, DMSA scan is suggested. Keywords: Urinary Tract Infections; DMSA (Dimercaptosuccinic Acid); Renal scars; Pediatrics.